Tumor classification using ultra-wideband (UWB) : late-time tumor response - Koh, Ling Ling. (2011)
In this project, the feasibility of tumour classification using Ultra-Wideband (UWB) late–time tumour response is investigated. This report summarizes the findings and evaluates the accuracy of the technique by studying how the UWB late-time breast tumour backscatter responses are affected by the morphology of the tumour. The backscatter responses are then processed and classified using neural networks.